Psychological Safety and Its Influence on Innovation in High-Performance Teams - Ahmed, Irfan; Mangi, Imtiaz Ali; Muzammil, Khadija (ACADEMIA International Journal for Social Sciences, 2025)
This study examined the relationship between psychological safety and innovation behavior in high-performance teams, with a focus on the mediating roles of voice behavior and risk tolerance. A cross-sectional survey design was used with a sample of 250 employees from high-performance teams in technology, healthcare, and financial services sectors. Validated measures assessed psychological safety (Edmondson, 1999), innovation behavior (Scott & Bruce, 1994), voice behavior (Van Dyne & LePine, 1998), and risk tolerance (Sitkin & Pablo, 1992). Hierarchical multiple regression analyses indicated that psychological safety significantly predicted innovation behavior (β = .58, p < .001), explaining 47% of variance in the outcome. Voice behavior (β = .27, p < .001) and risk tolerance (β = .21, p < .001) each partially mediated this relationship, with bootstrapped indirect effects confirming significance of both pathways. These findings highlight the strategic importance of psychologically safe team climates as preconditions for the creative risk-taking and proactive communication through which high-performance teams sustain innovative capacity.